The Relationship between Spiritual Health and Job Satisfaction among the Employees of the Legal Medicine Organization - Ahmad Shojaei Baghini; Abdorrazagh Barzegar; Abdoraoof Adibzadeh; Hamid Reza Daneshparvar; Armindokht Ahmadi; Seyed Mehdi Saberi (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Employees' job satisfaction is one of the most important issues in the field of organization's human resources and their spiritual health. It is also one of the essential aspects of people's health and well-being. The goal of this study was to investigate the relationship between Spiritual Health and Job Satisfaction in Legal Medicine staff. Methods: This descriptive-correlational study was carried out among the staff of Legal Medicine Organization in Iran. Data collection instruments included questionnaires of spiritual health, job satisfaction, and demographic information. A total of 321 questionnaires were completed and investigated. Descriptive statistics and Pearson correlation test were run by SPSS 16 for data analysis. The significance level of the test was set at 5%. Results: The highest mean was related to job satisfaction (53.50), while the lowest was attributed to salary satisfaction (19.72). A significant association was found between job satisfaction and spiritual health (p = 0.049, r = 0.102). Moreover, significant associations were observed between spiritual attitude towards God and job satisfaction (p = 0.032, r = 0/120), spiritual attitude to self and job satisfaction (p = 0.022, r = 0/128), spiritual health and satisfaction of the supervisor (p = 0.020, r = 0.139), as well as spiritual attitudes towards God and satisfaction of supervisors (p = 0.035, r = 0.118)  and colleagues (p = 0.042, r = 0.114). Conclusion: Increase of the staff spiritual attitude can promote their spiritual health. Therefore, conducting up-to-date scientific courses on spirituality training can be effective in planning for the promotion of spiritual health, job satisfaction, and performance among the organization's staff.